Marketing Channels of Fresh Longan in Chiang Mai Province - Auttarat, Werapong; Yooyen, Ayooth; Sumritsakun, Chaiyot; Awirothananon, Thatphong (RMUTL Journal of Business Administration and Liberal Arts, 2018)
This study aims to study the fresh longan marketing channels of farmers and entrepreneurs in Chiang Mai and problems encountered in fresh longan marketing channels in Chiang Mai province. In-depth interviews were used in this study in order to collect data of five domestic traders and three exporters. In addition, questionnaires were used to collect data from 400 farmers. Results of the study revealed that marketing channels could be divided into levels 3, 4, and 5. The members of marketing channels consisted of farmers, agents/middlemen, establishment, exporters, and destination markets. Each entrepreneur firm had different structure’s members in accordance with a number of the members, and necessity of various activities operation. Meanwhile, the farmers will distribute the products to middlemen. But if sell longan in more than one form will distribute the products to middlemen according to the form of distribution. The most attention to the purchase price as well. Regarding problems encountered in fresh longan marketing channels, it was found that are inside marketing channels. The most it involved product arrangement of workers and lack of product checking. This was because the workers and the farmers still lacked of experience in product arrangement as well as knowledge and understanding. Importantly the problem found most by the farmers was being taken advantage by the middleman.